Characteristics of Book Trade - Usmanova Nigina Marupovna (Researchparks Publishing, 2021)
Raising the morale of young people in our country and a meaningful organization of their leisure time, raising the morale of our youth, organizing systematic work to popularize reading among them, and developing the book trade. To understand the importance of the book trade as an economic system, it is necessary to improve its mechanism for increasing book production.